Experiment on Decomposition of Disposable Mask Waste Using Acid Liquid - Anis Ayu Arinda; Mitoriana Porusia (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The COVID-19 pandemic has led to an increase in disposable mask usage, raising environmental concerns due to improper disposal. This research aims to investigate the decomposition of disposable mask waste, specifically duckbill masks, by immersing them in 32% HCl and 98% H2SO4 solutions. This research uses experimental research methods for processing mask waste using the method of immersion in 32% HCl solution and immersion in 98% H2SO4. Fifty grams of mask waste were soaked in 1000 ml of each acid solution for periods of 1, 2, 3, and 4 weeks, with four replications for each time period, and water used as a control. After soaking, the masks were dried and re-weighed to assess weight loss. The data were analyzed using T-tests and ANOVA with SPSS 26. Results showed that after 4 weeks, H2SO4 reduced mask mass by 26%, while HCl achieved a 22% reduction. In the first week, H2SO4 reduced the weight by 3 grams, increasing to a total reduction of 13 grams by the fourth week. Similarly, HCl reduced the mask weight by 2 grams in the first week, with a total reduction of 11 grams by the end of the experiment. The findings suggest that H2SO4 is more effective than HCl in degrading disposable mask waste, offering a potential solution for managing mask waste environmentally. For the local government, it is necessary to make efforts to socialize the community in order to broaden their knowledge regarding the management of disposable mask waste so that the volume of mask waste stockpiles can be reduced and can be more beneficial. Keyword: Disposable Mask waste, Decomposition, HCL, H2SO4, Acid Liquid